THE ROUANET LAW IN BROADWAY PRODUCTIONS AND CELEBRITY THEATER - Mega, Vinícius Mizumoto (Seven Editora, 2025)
The chapter aims to show, through interviews with representatives of private companies and public institutions, directors of projects sponsored and made unfeasible through the Rouanet Law and a quantitative survey of plays sponsored in 2011 through the Rouanet Law's tax waiver, the existence of a concentration of Rouanet Law tax exemption resources on Broadway productions and on actors and directors known to the media to the detriment of authors and directors and actors unknown to the press. In this way, the big companies benefit shows that give a financial return and institutional marketing, the entertainment culture that seeks to entertain and please the “general public”. A survey by the Ministry of Culture found that 50% of funding is concentrated in just 3% of applicants. The theoretical framework was drawn from authors such as Adorno; Horkheimer; Abreu; Barichello; Barbalho; Botelho; Bourdieu; Coelho; Cruz; Debord; Fragoaz; Katz; Moreira; Ortiz; Rubim.DOI: https://doi.org/10.56238/sevened2025.002-006